(3GdeMGSHI GdeJhSWI (B:s (3GdeaGgje heYGjjQ GdbjGS hGdEaUGM GdeMGSHj (B/s - (3GdUHGf, eMeO SejQs; (3CMeO, CHh GdMSf Ydj s ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 1998)
(3jJfGhd gPG GdcJGH HYV ehVhYGJ GdeMGSHI GdeJhSWI hbO Je JbSje gPG GdcJGH Edi KdGK eOGNd HGdEVGaI Edi JeGQjf aj GdeMGSHIs
Keywords: (3GdbjGSs; (3GdeMGSHIs